International marketing studies in banking and finance: a comprehensive review and integrative framework - Battisti, Enrico; Graziano, Elvira Anna; Leonidou, Erasmia; Stylianou, Ioanna; Pereira, Vijay (My University, 2021)
Purpose: The purpose of this paper is to provide a comprehensive analysis of international marketing (IM) studies within the context of banking and finance (B&F), articulating its significance and relevance in view of the growing influence of this topic in the global economy. Design/methodology/approach: The systematic review methodology was applied for the purpose of identifying the relevant studies, as well as the key themes and dominant concepts. In establishing a quality benchmark for the review results, the final sample included articles published in peer-reviewed academic journals ranked 3, 4 and 4* in the ABS 2018 journal list, a common practice in existing systematic review studies. Findings: Based on a systematic review of 66 studies, the results reveal that the topic has grown and continues to expand within the broader IM field over the past 35 years. From the proposed integrative framework, it is possible to identify the links between several IM subjects and B&F topics, highlighting a different intensity of studies and in-depth analysis among the various specific areas investigated. Originality/value: The authors map and critically evaluate the extant IM research in B&F context for the purpose of increasing its coherence, scope and international dimension. Finally, the authors present a multidisciplinary, integrative framework that organizes the existing literature, provides the theoretical basis for scholars to further expand the boundaries of the domain and serves as a guiding tool for practitioners.
Keywords: Banking and finance; Comprehensive review; Integrative framework; International marketing research; Systematic literature review